1998
DOI: 10.2190/kv0t-g9ej-yfdu-yy08
|View full text |Cite
|
Sign up to set email alerts
|

Portfolio Assessment of Instructional Technology

Abstract: This article addresses one specific method of authentic assessment, portfolio assessment, by applying this method in two case studies assessing learning of instructional technology. Suggestions for practitioners who wish to use this method are provided at the conclusion of the article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…This chapter investigated the extent and efficacy of e-portfolios for demonstrating PSTs' development of the teaching standards. This chapter defined eportfolios and introduced different types, including the presentation e-portfolio, outcome e-portfolio, documental e-portfolio, assessment e-portfolio, process eportfolio, record e-portfolio, work e-portfolio, course e-portfolio, reflective eportfolio, structured e-portfolio, and e-learning portfolio (Carlson, 1999;Cole, Ryan, & Kick, 1995;Danielson & Abrutyn, 1997;Greenberg, 2004;Tillema & Smith, 2000). The most relative e-portfolio-based activities that underpin e-portfolio implementation in higher education have been introduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This chapter investigated the extent and efficacy of e-portfolios for demonstrating PSTs' development of the teaching standards. This chapter defined eportfolios and introduced different types, including the presentation e-portfolio, outcome e-portfolio, documental e-portfolio, assessment e-portfolio, process eportfolio, record e-portfolio, work e-portfolio, course e-portfolio, reflective eportfolio, structured e-portfolio, and e-learning portfolio (Carlson, 1999;Cole, Ryan, & Kick, 1995;Danielson & Abrutyn, 1997;Greenberg, 2004;Tillema & Smith, 2000). The most relative e-portfolio-based activities that underpin e-portfolio implementation in higher education have been introduced.…”
Section: Discussionmentioning
confidence: 99%
“…As presented in chapter 2, there are different types of e-portfolios available for educational purposes including: documental e-portfolio; assessment e-portfolio; process e-portfolio; record e-portfolio; work e-portfolio; course e-portfolio; reflective e-portfolio; structured e-portfolio; e-learning portfolio; and developmental e-portfolios (Carlson, 1999;Cole, Ryan, & Kick, 1995;Danielson & Abrutyn, 1997;Greenberg, 2004;Tillema & Smith, 2000). Tosh, Light, Fleming, and Haywood (2005) suggested that an institution, or a course, is required to examine the learning outcome of using e-portfolios to ensure that the e-portfolio is aligned with the rest of the course.…”
Section: Integration Of the E-portfolios Into The Unitmentioning
confidence: 99%
“…Students are able to present themselves electronically to graduate school admissions officers and future employers. At MEC, students use a process and product format to create their ePortfolios (Carlson, 1998). In process/working, ePortfolio students collect their work throughout their enrollment at MEC.…”
Section: Current Uses Of Eportfolio At Medgar Evers Collegementioning
confidence: 99%